Alga Ecklonia bicyclis, Tribulus terrestris, and Glucosamine Oligosaccharide Improve Erectile Function, Sexual Quality of Life, and Ejaculation Function in Patients with Moderate Mild-Moderate Erectile Dysfunction: A Prospective, Randomized, Placebo-Controlled, Single-Blinded Study. (20th July 2014) - Sansalone, Salvatore; Leonardi, Rosario; Antonini, Gabriele; Vitarelli, Antonio; Vespasiani, Giuseppe; Basic, Dragoslav; Morgia, Giuseppe; Cimino, Sebastiano; Russo, Giorgio Ivan
Abstract : We aimed to evaluate the efficacy of oral therapy with alga Ecklonia bicyclis, Tribulus terrestris, and glucosamine oligosaccharide (Tradamix TX1000) in patients with erectile dysfunction (ED) at 3 months of follow-up. From January 2013 to September 2013, 177 patients diagnosed with mild-moderate ED (IIEF-EF < 26) were enrolled in this multicenter, single-blinded, placebo-controlled study and randomized in Group A (Tradamix, n = 87 ) and Group B (placebo, n = 90 ). Penile color Doppler ultrasound measures, IIEF-15 questionnaire, male sexual health questionnaire-ejaculation disorder (MSHQ-EjD), and sexual quality of life (SQoL-M) were collected. We observed significant changes of the IIEF-15 in Group A (mean difference: 11.54; P < 0 . 05 ) at 3 months versus Group B (P < 0.05 ). PSV (P < 0.05 ), IIEF-intercourse satisfaction (P < 0.05 ), IIEF-orgasmic function (mean P < 0.05 ), IIEF-sexual desire (P < 0.05 ), IIEF-overall satisfaction (P < 0.05 ), MSHQ-EjD (mean difference: 1.21; P < 0.05 ), and SQoL-M (mean difference: 10.2; P < 0.05 ) were significantly changed in Group A versus baseline and Group B. Patients with moderate arterial dysfunction showed significant increase of PSV (P < 0.05 ), IIEF-EF (P < 0.05 ), MSHQ-EjD (P < 0.05 ), and SQoL-M (P < 0.05 ) in Group A. Therapy with Tradamix improves erectile and ejaculation function and sexual quality of life in patients with mild-moderate ED and in particular for those with moderate arterial dysfunction.